Evaluation on efficacy and safety of tyrosine kinase inhibitors plus radiotherapy in NSCLC patients with brain metastases - Luo, Shuimei (Oncotarget, 2015)
OBJECTIVE: The study was designed to evaluate the efficacy and safety of tyrosine kinase inhibitors (TKIs) plus radiotherapy in patients with brain metastases (BM) of non-small cell lung cancer. METHODS: Medline PubMed, Google Scholar, Web of Science, Oxford Journals Collection, clinical trials and current controlled trials were searched to identify relevant publications. After screening literature and undertaking quality assessment and data extraction, the meta-analysis was performed using RevMan5.3 software. RESULTS: Eight controlled trials (980 participants) were included in the study. Compared with radiotherapy without TKIs (non-TKI-group), TKIs plus radiotherapy (TKI-group) had a significant benefit on objective response rate (ORR) (RR = 1.56, 95%CI [1.25,2.03]; P =0.0008), significantly prolonged the time to central nerves system progression (CNS-TTP) (HR =0.58, 95% CI [0.35, 0.96]; P =0.03) and median overall survival (MOS) (HR =0.68, 95% CI [0.47, 0.98]; P =0.04) of NSCLC patients with BM. There was no significant difference in overall severe adverse events (Grade≥3) (RR = 1.49, 95% CI [0.88,2.54]; P = 0.14) between two groups. CONCLUSION: This meta-analysis showed TKI-group produced superior response rate when compared with non-TKI-group. TKIs plus radiotherapy significantly prolong the CNS-TTP and MOS of patients without enhancing overall severe adverse events.